Empowering Arabic Educators in the Digital Era: Evaluating an AI-TPACK Professional Training Model - Mokhamad Azis Aji Abdilah; Subandji; Faizal Nur Abidin; Siti Aisyah; Esa Saputro; Fouad Larhzizer (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
The digital competence of Arabic language teacher in Madrasah Tsanawiyah (MTs) in Sukoharjo remains low, particularly in developing interactive electronic student worksheets (E-LKPD). This study aims to test the effectiveness of AI-TPACK based training, integrating generative AI (ChatGPT and Teks To Speech) and Liveworksheets apps, in improving teacher competence. A quantitative approach with a quasi experimental one group design was employed. The sample consisted of 20 Arabic language teachers selected through purposive sampling from 11 different MTs. Data were collected using a validated questionnaire (Aiken’s V=0.87) and analyzed using Paired Sample T-Test and N-Gain scores. The results showed a significant increase across all competency variables (Sig. < 0.05), with an average N-Gain score of 0.59 (Moderately Effective). The highest increase occurred in AI-TPACK integration mastery (N-Gain = 0.76, Highly Effective). However, field implementation remains constrained by network infrascrtucture and device factors. These findings inply that the AI-TPACK training model is a strategic solution for developing teacher competence in the digital era.